Analisis Pengembangan Potensi Sumingkir Sebagai Upaya Merintis Desa Wisata Berbasis Lingkungan Dan Religi - Amanda, Virna Tria; Annisya Prastica Lestari; Farhan Fadlillah Hikam (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The tomb of KH RAGA SUMINGKIR is a tomb located in Rajadatu village, Cineam sub-district, which is one of the community leaders in Rajadatu village. The tomb of KH Raga Sumingkir has its own uniqueness, which only uses ordinary stones and does not use tombstones, of course, it is very different from funerals in general which mostly use tombstones, especially like public figures who usually use small buildings.This research intends to find out how the development strategy of religious tourism objects at the Tomb of KH Raga Sumingkir. This research is a field research (field research) by taking the research location in the tomb of Kh Raga Sumingkir in Rajadatu village, Cineam sub-district, Tasikmalaya district. The research data are qualitative data in the form of primary and secondary data. The data were obtained through observation, interviews, and documentation. The data that has been collected is then analyzed using qualitative descriptive analysis method.